Anthropogenic Effects on the Contemporary Sediment Budget of the Lower Rhine‐Meuse Delta Channel Network. Issue 7 (29th June 2021) - Cox, J. R.; Huismans, Y.; Knaake, S. M.; Leuven, J. R. F. W.; Vellinga, N. E.; van der Vegt, M.; Hoitink, A. J. F.; Kleinhans, M. G.
Abstract: Deltas and estuaries worldwide face the challenge of capturing sufficient sediment to keep up with relative sea‐level rise. Knowledge about sediment pathways and fluxes is crucial to combat adverse effects on channel morphology, for example, erosion which enhances bank collapse and increasing tidal penetration. Here, we construct sediment budgets which quantify annual changes for the urbanized Rhine‐Meuse Delta of the Netherlands, a typical urban delta experiences changing fluvial and coastal fluxes of sediment, engineering works and dredging and dumping activities. The delta shows a negative sediment budget (more outgoing than incoming sediment) since the 1980s, due to anthropogenic intervention. Following a large offshore port expansion, dredging in ports and harbors in the region has doubled in the past 5 years, likely due to the induced change in net sediment fluxes. In addition, the deeper navigation channels, ports, and harbors are now trapping siltier sediment, changing the sediment composition in the mouth. The removal of sediment by dredging is adverse to the necessity for sediment in heavily eroding branches. To allow for sustainable sediment management in the future and to cope with sea‐level rise, further measurements are required to properly quantify the amount of incoming sediment at the boundaries of the system and the internal mechanisms of transport. The varied response of the branches has important consequences for navigation, ecology and flood safety and management of the sediment in the system. These effects will be of pivotal importance in coming decades with similar implications for many urbanized deltas worldwide. Plain Language Summary: Deltas need sufficient sediment to grow with sea‐level rise and counteract natural and human‐induced subsidence. A sediment budget quantifies if a delta is net gaining sediment or if it is losing sediment over a long time period. The Rhine‐Meuse Delta (RMD) has a negative budget: Its entire network of channels is losing sediment annually. The reason for this negative budget is the high amounts of sand and mud removed for navigation to inland ports and from harbors which are periodically dredged. As a result, some of the channels in the area degrade rapidly, which causes issues for river management and dynamics including water quality, flood safety, and ecology. Other deltas worldwide are managed similarly to the RMD and will therefore face the same sediment issues. A strategy is required to deal with channel degradation and find ways to maintain sediment in the system. Key Points: Human impacts on delta channels can be quantified using empirical relations between tidal prism and cross‐section area in delta channels Establishing sediment budgets for delta channel networks requires data concerning both sand and mud, which are jointly subject to dredging Reduced sediment input to deltas may partially be compensated for by influx of marine sediment, which is a large source of uncertainty